2023
DOI: 10.3390/diagnostics13071276
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Gastric Cancer: Current Practice and Future Perspectives

Abstract: Gastric cancer represents one of the most common oncological causes of death worldwide. In order to treat patients in the best possible way, the staging of gastric cancer should be accurate. In this regard, endoscopy ultrasound (EUS) has been considered the reference standard for tumor (T) and nodal (N) statuses in recent decades. However, thanks to technological improvements, computed tomography (CT) has gained an important role, not only in the assessment of distant metastases (M status) but also in T and N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
0
0
Order By: Relevance
“…Endoscopic ultrasound (EUS) provides detailed images of the gastrointestinal tract and nearby structures, aiding in the evaluation of tumour depth and lymph node involvement. Blood tests may be conducted to assess markers associated with gastric cancer, such as carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA 19-9) [ 20 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS) provides detailed images of the gastrointestinal tract and nearby structures, aiding in the evaluation of tumour depth and lymph node involvement. Blood tests may be conducted to assess markers associated with gastric cancer, such as carcinoembryonic antigen (CEA) and carbohydrate antigen 19-9 (CA 19-9) [ 20 , 21 ].…”
Section: Reviewmentioning
confidence: 99%
“…Although EUS is reliable for investigation of depth of most small and non-ulcerated gastric lesions, it has been shown to have poor accuracy determining the depth of gastric lesions greater than 20mm, those with ulceration, and/or non-flat morphology, which usually make up the expanded criteria outlined by JGES[ 45 , 46 ]. CT of the abdomen can assist in identifying associated lymph nodes and metastasis[ 47 ]. Despite the availability of various diagnostic techniques, there are no clear guidelines on the approach to diagnosing GCP.…”
Section: Gastric Cystica Profunda: Workup and Managementmentioning
confidence: 99%
“…EUS can visualize the entire gastric wall and has higher accuracy in distinguishing EGC from advanced gastric cancer. EUS has become the preferred tool for local staging of gastric cancer nowadays [37]. Previous studies have reported an accuracy of 67% to 72% in determining the depth of infiltration by EUS for EGC.…”
Section: Early Gastric Cancermentioning
confidence: 99%